The provision of recipes and single-use herb/spice packets to increase egg and protein intake in community-dwelling older adults: a randomised controlled trial. Issue 8 (1st June 2021) - van den Heuvel, E; Murphy, JL; Appleton, KM
Abstract: Objective: This study investigated the impact of recipe and single-use herb/spice packet provision on egg intake and protein intake in community-dwelling individuals aged over 55 years. Design: Using a randomised-controlled intervention design, 100 older adults were randomised to receive ( n 53) or not receive ( n 47) high-protein egg-based recipes and herb/spice packets through the post for 12 weeks, from June to December 2016. Egg intake, protein intake, adverse events, lean body mass and functional measures of lean body mass were measured at baseline, after the 12 weeks and after a further 12 weeks. Setting: Bournemouth, UK. Participants: Community-dwelling older adults. Results: Intention-to-treat data were analysed using regression, controlling for various demographic and lifestyle characteristics. Ninety-three individuals (intervention, n 50; control, n 43) completed assessments at all three time points. Egg intakes increased by end of intervention in both groups (mean: 4–5 eggs/month). After a further 12 weeks, higher egg intakes were sustained in the intervention group, while egg intakes in the control group returned to baseline levels (between-group difference: β = −0·124, P = 0·047). No differences were found in other measures (largest β = −0·106, P = 0·12). Conclusions: The provision of high-protein egg-based recipes and single-use herb/spice packets over 12 weeks increased egg intakes up to 12 weeks after end of intervention. Other factors may explain increased egg intakes during the intervention, but the sustained effects most plausibly result directly from recipe provision. Limited effects in other measures suggest that the recipes may have replaced as opposed to added to existing protein intakes.